Effects of irradiation on polyethyleneterephthalate(PET) fibers impregnated with sensitizer. Issue 3 (4th March 2018) - Zhu, Shifeng; Shi, Meiwu; Tian, Mingwei; Qu, Lijun; Chen, Guohua
Abstract: Polyethylene terephthalate(PET) is difficult to be irradiation cross-linked at low dose for the aromatic groups. In this paper, trimethylolpropane triacrylate (TMPTA) was incorporated in PET fibers to sensitize the cross-linking. Changes in PET fibers subjected to electron beam irradiation at dose up to 200 kGy and dose rate 12 kGy/s were investigated by gel content, scanning electron microscopy, differential scanning calorimetry, X-ray diffraction, thermal gravimetric analysis and X-ray photoelectron spectroscopy. The gel content was 0.14% at dose of 60 kGy and it arrived at the maximum value 0.53% at 100 kGy. Irradiated fibers showed a decrease in the breaking strength and an increase in the elongation at break. The crystal form of PET fibers had not been changed and crystallinity decreased 28% with the increasing dose. The melting temperature shifted from the original 254.28 °C to 253.44 °C. The thermal stability and the amount of non-volatile residue at 800 °C increased at dose of 100 kGy. XPS analysis indicated that the number of C-C band increased to prove the occurring of cross-link. The surface of PET fibers got rougher after irradiation and the anti-dripping property had not been improved effectively for the low degree of cross-linking.